Ultra-rare Disease and Genomics-Driven Precision Medicine - Sangmoon Lee; Murim Choi (Genomics & Informatics)
Since next-generation sequencing (NGS) technique was adopted into clinical practices, revolutionary advances in diagnosing rare genetic diseases have been achieved through translating genomic medicine into precision or personalized management. Indeed, several successful cases of molecular diagnosis and treatment with personalized or targeted therapies of rare genetic diseases have been reported. Still, there are several obstacles to be overcome for wider application of NGS-based precision medicine, including high sequencing cost, incomplete variant sensitivity and accuracy, practical complexities, and a shortage of available treatment options.